Harnessing the patient voice in prostate cancer research: Systematic review on the use of patient‐reported outcomes in randomized controlled trials to support clinical decision‐making. (25th April 2020) - Van Hemelrijck, Mieke; Sparano, Francesco; Moris, Lisa; Beyer, Katharina; Cottone, Francesco; Sprangers, Mirjam; Efficace, Fabio
Abstract: Background: Given the growing importance of patient‐reported outcomes (PROs) as part of "big data" in improving patient care, there is a need to provide a state‐of‐the‐art picture of the added value of using PROs in prostate cancer (PCa) randomized controlled trials (RCTs). We aimed to synthetize the most recent high‐quality PRO evidence‐based knowledge from PCa RCTs and to examine whether quality of PRO reporting in PCa research improved over time. Methods: We conducted a systematic literature search using PubMed, from April 2012 until February 2019. For benchmarking purposes, we also included RCTs identified in our previously published review of RCTs (2004‐2012). Methodology for study identification and evaluation followed standardized criteria and a predefined data extraction form was used to abstract information. PRO quality of the studies was evaluated using the International Society of Quality of Life Research (ISOQOL) recommended criteria. Results: A total of 55 new RCTs were published between April 2012 and February 2019. About 24 (43.6%) RCTs were found to be of high‐quality regarding PRO assessments. Of these, 13 (54.2%) have been reported in the most recent European Association of Urology (EAU) PCa Guidelines. Overall QoL and sexual, urinary, and bowel function were the most commonly reported PROs. FACT‐P, EPIC‐26, and EORTC QLQ‐C30 and/or its module PR25 were most frequently used as measurement tools. An overall improvement in the completeness of PRO reporting was noted over time. Conclusion: Many PRO trials are currently not included in the EAU guidelines. Our findings suggest that there has to be a better consensus on the use of PRO data for PCa patients, which will then be reflected in the PCa Guidelines and future data collection. Homogeneity in PROs collection and measurement tools will in turn enable "big data" Consortia to increase the patients' voice in clinical research. Abstract : Patient reported outcomes need to become the standard in prostate cancer RCTs. There is need for consensus on the use of PRO data, which will reflect their use in the guidelines and future data collection.